KUALITAS AUDIT INTERNAL UNTUK KINERJA PERUSAHAAN: TINJAUAN LITERATUR SISTEMATIKA - Silviani, Amanda Agnes; Gusnardi, Gusnardi; Andreas, Andreas (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2024)
Identifying weak points in financial management and control systems as well as potential opportunities to improve company performance is the responsibility of an internal auditor. Independent, professional, and competent internal auditors are able to make a positive contribution to operational efficiency, risk management, and corporate accountability. In addition, the internal auditor's objectivity in providing improvement recommendations can improve management's follow-up on audit findings. This study aims to explore the factors that influence the quality of internal audit to improve company performance.  The research method in this study is in the form of a literature review. Seven journals were obtained that became literature fists using VOSviewer and Publish or Perish software. The results showed that there are several internal factors and external factors that affect the quality of internal audit. The findings of this study provide practical implications for companies in improving the quality of their internal audits as a means to improve company performance. Company management is expected to provide adequate support to the internal audit function and ensure internal auditors have sufficient skills and resources to perform their duties properly.